Análise comparada da saúde bucal do idoso na cidade de Araçatuba-SP, Brasil - Monti, Lira Marcela [UNESP]; Justi, Mirella Martins [UNESP]; Farjado, Renato Salviato [UNESP]; Zavanelli, Adriana Cristina [UNESP] (Universidade do Estado do Rio Janeiro, 2019)
Based on health public policies for the elderly, established by the Brazilian Health Ministry, this paper analyses the elderly’s oral health program, showing the Brazilian reality, which lacks preventive, curative and educational treatments. This research created an instrument to assess the oral situation of the elderly in Araçatuba city, through questions on the socioeconomic profile, oral situation, and use of services rendered by the municipal health service. We searched for data to subsidize projects of public policies that meet this population’s needs. Results showed that more than 80% of seniors are toothless, 77% use dental prostheses despite the fact that most live on their minimum-wage pensions, which many times are the main family income and have no access to specific public rehabilitation services and are illiterate. We come to the conclusion that the elderly in Araçatuba still do not have access to the preventive, curative, educational and rehabilitation treatments.

Com base nas políticas públicas de saúde de atenção ao idoso, preconizadas pelo Ministério da Saúde, este artigo analisa a atenção à saúde bucal do idoso, ilustrando uma realidade brasileira quanto à falta de tratamentos preventivos, curativos e educacionais. Este trabalho estruturou um instrumento de avaliação para observar a situação bucal da população acima de 60 anos da cidade de Araçatuba, através do qual, com perguntas quanto ao perfil socioeconômico, situação bucal e utilização dos serviços prestados pela rede municipal de saúde, buscaram-se dados para subsidiar projetos de políticas públicas que contemplem as necessidades levantadas. Os resultados mostraram que mais de 80% dos idosos são desdentados e 77% utilizam próteses dentárias, apesar de a maioria viver da aposentadoria de um salário mínimo, que muitas vezes é a principal fonte de renda familiar, e não ter acesso a serviços específicos de reabilitação na rede pública de saúde. Além disso, a maioria é iletrada. Conclui-se que os idosos de Araçatuba não tiveram e continuam não tendo acesso aos tratamentos preventivos, curativos, reabilitadores e educativos.
Compared analysis of elderly’s oral health in Araçatuba-SP city, Brazil
Keywords: aged, health policy, geriatric dentistry, oral health aged; oral health; health services for aged; geriatric dentistry; public policies; araçatuba city; idoso; política de saúde, odontogeriatria, saúde bucal. idoso; saúde bucal; serviços de saúde para idosos; odontologia geriátrica; políticas públicas; araçatuba